The projection from the prelimbic cortex to the ventral tegmental area negatively regulates 5-HT-induced itch-scratching and positively regulates itch-related aversion in rats - Xing-Yu Lu; Jun-Fei Teng; Juan Yao; Xuan Li; Bing Wu; Xue-Qiang Hu; Ping Wang; Xiao-Qian Jiang; Jian-Feng Sui; Ke-Hui Hu; Yue-Ming Xu; Shu-Lei Liu (Brain Research Bulletin, 2025)
Direct and indirect evidence suggests that the prelimbic cortex (PrL) and the ventral tegmental area (VTA) are the key brain regions involved in the regulation of itch sensation and itch-related emotions. The PrL projects widely to various cortical and subcortical brain regions, with the VTA being one of the main targets of PrL descending projections. However, the differential roles of the PrL-VTA pathway in the regulation of itch sensation and itch-related emotion remain unclear. In this study, we investigated 5-HT-induced conditioned place aversion (CPA) and itch-scratching behavior in rats after pharmacogenetic inhibition of PrL-VTA projection activity. Pharmacogenetic inhibition of a subpopulation of PrL glutamatergic neurons projecting to the VTA increased 5-HT-induced itch-scratching behavior but alleviated the conditioned place aversion behavior accompanying acute itch, indicating that the descending pathway from the PrL to the VTA negatively controls itch sensation but positively regulates itch-related negative emotion. GABAergic and DAergic neurons in the VTA are potentially responsible for mediating the opposite regulatory effects of PrL-VTA projections on itch sensation and emotion, respectively. These results are helpful for further understanding the neuroregulatory mechanisms of different components of itch.